2000
DOI: 10.1016/s0959-8049(00)00277-x
|View full text |Cite
|
Sign up to set email alerts
|

Germ line BRCA1 and BRCA2 gene mutations in Turkish breast cancer patients

Abstract: Germ line BRCA1 and/or BRCA2 mutations were screened in 50 Turkish breast and/or ovarian cancer patients composed of hereditary, familial, early onset and male cancer groups. Genomic DNA samples were tested by heteroduplex analysis and DNA sequencing. Two truncating BRCA2 mutations, one novel (6880 insG) and one previously reported (3034 delAAAC), were found in two out of six (33%) hereditary breast and/or ovarian cancer patients. A novel truncating (1200 insA) and a missense (2080A3G) BRCA1 mutation was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…However, the molecular genetic basis of inherited predisposition to breast cancer in non-BRCA1, non-BRCA2, non-LiFraumeni individuals is not known (Nathanson et al, 2001). We therefore sought germ-line mutations in Chk2 in a panel of breast cancers previously characterized for BRCA1 status (Ozdag et al, 2000). Other than three individuals heterozygous for a previously described non-coding polymorphism, no deviations from the published coding sequence of Chk2 were detected in the germ-line of these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the molecular genetic basis of inherited predisposition to breast cancer in non-BRCA1, non-BRCA2, non-LiFraumeni individuals is not known (Nathanson et al, 2001). We therefore sought germ-line mutations in Chk2 in a panel of breast cancers previously characterized for BRCA1 status (Ozdag et al, 2000). Other than three individuals heterozygous for a previously described non-coding polymorphism, no deviations from the published coding sequence of Chk2 were detected in the germ-line of these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Normal tissue was available for two of the cases with mutations and sequencing of DNA from this revealed that the mutations were somatically acquired rather than germ- Absence of germ-line mutations in hereditary, familial, early onset and male breast cancer Germ-line mutations in Chk2 have been described in individuals with the Li-Fraumeni syndrome (Bell et al, 1999) and in a very small number of non-BRCA1, non-BRCA2 hereditary breast cancers (Allinen et al, 2001;Vahteristo et al, 2001). We therefore analysed the germ-line structure of Chk2 in 45 individuals with various forms of breast cancer, in whom the BRCA1 and BRCA2 status has been previously described (Ozdag et al, 2000). In these cases, direct sequencing of genomic DNA isolated from peripheral blood lymphocytes detected the codon 84 polymorphism in three of the 45 cases, but no germ-line mutations in any of the cases.…”
Section: Novel Somatic Chk2 Mutations Are Detected In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNAs were isolated as described previously (Unsal et al, 1994;Yakicier et al, 1999). The exon 3 sequence of b-catenin was studied for base substitutions and small insertion/deletions by SSCP as described previously (Ozdag et al, 2000), as well as by direct DNA sequencing. In addition, the b-catenin gene region encompassing exons 2 to 4 was studied for larger deletions, essentially as described by Koch et al (1999).…”
Section: B-catenin Mutation Analysismentioning
confidence: 99%
“…Different patient selection criteria and different mutation detection methods were applied, no predominant mutation was observed in Turkish population 15,[17][18][19][20][21][22][23][24][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%